Seeing Another Viewpoint: Antecedents and Outcomes of Employee Perspective Taking - Parker, Sharon K.; Axtell, Carolyn (Academy of Management Journal, 2001)
Supplier perspective taking, whereby an internal customer adopts the perspective of an internal supplier, was investigated. Two dimensions were assessed: positive attributions and empathy. Supplier perspective taking was associated with team leader ratings of employees? contextual performance. Production ownership and integrated understanding predicted supplier perspective taking and were in turn predicted by job autonomy, Interaction with suppliers contributed to supplier perspective taking directly and indirectly. These findings suggest two ways to enhance supplier perspective taking and hence contextual performance: increase employee interaction with suppliers and enrich job content.